Pancreatic fistula following pancreatoduodenectomy. Evaluation of different surgical approaches in the management of pancreatic stump. Literature review. (September 2015) - Conzo, G.; Gambardella, C.; Tartaglia, E.; Sciascia, V.; Mauriello, C.; Napolitano, S.; Orditura, M.; De Vita, F.; Santini, L.
Abstract: Pancreatoduodenectomy is the gold standard operation for malignant and benign diseases of the pancreas and periampullary region. Even if improvements in intensive care management and surgical technique have dramatically reduced postoperative mortality after pancreatic surgery, morbidity remains high (30–50%), also in specialized pancreatic units. In order to reduce postoperative complications, particularly pancreatic fistula, different surgical techniques and their modifications have been proposed. In order to determine the better management of the pancreatic stump after pancreatoduodenectomy, the Authors analysed and compared derivative – pancreaticojejunal, pancreaticogastrostomy – vs no-derivative technique – pancreatic stump closure (duct ligation or mechanical suture, duct occlusion by fibrin glue or cyanoacrylate). A systematic research of the English literature, including major meta-analysis articles, clinical randomized trials, retrospective studies and systematic reviews was performed, analysing the risk factors and the incidence of short-medium term postoperative complications. Up to now, even if derivative procedures are preferred as gold standard the best method to deal a pancreatic stump is still controversial and remains matter of research. Pancreatic surgeons must have more than one technique for managing the pancreatic remnant.